The Impact of The Doctrine of The Closed Door of Ijtihad on The Thought of Fazlurrahman: A Case Study of Islamic Law Teaching Methods in The Salafiyah Sabilul Muttaqin Boarding School in Mojokerto City - Marcella Nadhia Anggraeni (Postgraduate Program, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2023)
This research is motivated by observation data which shows that the ideal education is because it is able to touch all aspects and potential of students, but unfortunately education currently tends to be oriented towards the cognitive and matearilistic dimensions.The average orientation of education today is only used as a graduate or even to get a job. Therefore, this research seeks to discuss the method of teaching Islamic law at the Salafiyah Sabilul Muttaqin Islamic Boarding School. This can be seen from the teaching pattern of the YellowIslamic classic Book, especially the Book of Fiqh (Islamic Law) which is essentially a scientific thought or explanation of Islamic scientists or scholars on cases of sharia (Al-Quran and Al-Hadith). With the doctrine of the closure of ijtihad, the teaching model applied in traditional Islamic boarding schools is only a transfer of meaning (getting meaning from Arabic books) and explaining the content without any dialog or discussion. This article also examines how the doctrine of the closed door of ijtihad affects the teaching pattern of Islamic law at the Salafiyah Sabilul Muttaqin Islamic Boarding School. With the positive progress of technology and information as well as the many modern teaching models, there is a promising hope for Salafiyah Islamic Boarding Schools to improve their teaching patterns and develop into more modern without having to break down and leave their characteristics.